2007
DOI: 10.1007/s10705-007-9095-5
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of organic residues and chemical fertilizer to productivity of rain-fed lowland rice and to soil nutrient balances

Abstract: Low yields and high risk characterize many rain-fed lowland rice environments, including those in Laos. Drought and fluctuating soil-water conditions (from aerobic to anaerobic states) can limit productivity and the efficient use of applied nutrients. Although addition of organic matter may improve the efficiency of fertilizer use, on-farm residues, for example farmyard manure (FYM), rice straw and rice hulls, are, currently, poorly utilized in these systems. Single and multi-year experiments were designed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…These authors reported that the NRE observed on‐farm were lower and ranged from 30 to 40%. Under rainfed rice conditions in Asia, Linquist et al (2007) reported NRE values of 13 to 30%. The higher on‐farm NRE values found in California relative to Asia, may reflect improved water and fertilizer management practices, a higher yield potential in a Mediterranean climate and the use of more physiological N use efficient rice varieties.…”
Section: Resultsmentioning
confidence: 99%
“…These authors reported that the NRE observed on‐farm were lower and ranged from 30 to 40%. Under rainfed rice conditions in Asia, Linquist et al (2007) reported NRE values of 13 to 30%. The higher on‐farm NRE values found in California relative to Asia, may reflect improved water and fertilizer management practices, a higher yield potential in a Mediterranean climate and the use of more physiological N use efficient rice varieties.…”
Section: Resultsmentioning
confidence: 99%
“…Longterm manure application along with chemical fertilizers led to significantly higher values of soil available N compared to the other fertilization treatments. It has also been reported by many authors (Mann et al 2006;Linquist et al 2007;Shahid et al 2013) that the manure application leads to increase in soil available N and available P. However, higher levels of these soil nutrients were maintained when these nutrients were applied on long-term basis with the manure (Motavalli and Miles 2002). Unlike available N and available P, available K was the highest in NK + FYM treatment, followed by the NPK + FYM treatment, demonstrating the role of chemical fertilizers and organic manure in the supplementation of K in the soil.…”
Section: Basic Soil Properties After 41 Years Of Fertilizers and Manumentioning
confidence: 86%
“…Soil organic matter is central to sustaining rice crop production and application of organic manures is considered to be an important strategy for the build-up of carbon stock in flooded soils (IRRI 1984;Linquist et al 2007). Under tropical conditions, the turn-over rate of soil organic matter can be rapid (Katayal et al 2001).…”
Section: Introductionmentioning
confidence: 99%